SHALLOW TARGET FORWARD MODELLING SEISMIC DATA PROCESSING OPTIMALISATION USING CRS METHOD - GANI (NIM : 12404023), MUTIARA
Generally, shallow target has a limited fold coverage that makes the data difficult to process, moreover with the undulated subsurface condition. This case is a problem because the variant dip of the reflector is not included in the conventional seismic data processing parameter. Whereas the frequency of the source wavelet is band-limited which affect the seismic quality and resolution. The purpose of this final project is to find the design survey, optimum frequency, and the data processing method which can produce a good result for the undulated shallow target. Therefore, conventional seismic data processing and the CRS method were used. The CRS method calculate emergence angle, curvature of the normal wave, and the curvature of the NIP wave. A set of synthetic shallow target channel model with the variant survey seismic parameter and the frequency of the source wavelet was used to observe the CRS method. As result, a better reflector recovering compared against conventional processing sequence was observed.